1992
DOI: 10.1243/pime_proc_1992_206_138_02
|View full text |Cite
|
Sign up to set email alerts
|

Static and Dynamic Axial Crushing of Externally Reinforced Tubes

Abstract: The effect of axial impact on thin-walled circular tubes, which are reinforced externally by a glass fibre reinforced plastic (FRP) composite, is studied in this paper. The influence of circumferential reinforcement on the static and dynamic crushing behaviour of steel tubes is examined. The experimental results show that the crushing mode depends strongly on the circumferential reinforcement. All the reinforced tubes collapsed in a diamond mode with more intensive lobes than the corresponding non-reinforced o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Shin et al [ 38 ] and Wierzbicki et al [ 39 ] analyzed the energy absorption mechanism of hybrid tubes under axial compression and established the mean crushing force prediction model of hybrid square tubes and circular tubes with 90° circumferential fibers respectively, which were verified by experiments. [ 39,40 ] Bambach [ 41,42 ] derived the mean crushing force prediction expressions of CFRP‐metal hybrid square tube from a series of quasi‐static axial compression experiments and compared them with the experimental results. Zhang et al, [ 43 ] Wang and Lu, [ 44 ] also presented prediction models similar to Wierzbicki et al [ 39 ] The former put forward a formula for predicting the folding angle of SFE in the hybrid tubes, the latter took into account the influence of winding angles on energy absorption, and was also suitable for hybrid circular tubes under dynamic impact load.…”
Section: Introductionmentioning
confidence: 99%
“…Shin et al [ 38 ] and Wierzbicki et al [ 39 ] analyzed the energy absorption mechanism of hybrid tubes under axial compression and established the mean crushing force prediction model of hybrid square tubes and circular tubes with 90° circumferential fibers respectively, which were verified by experiments. [ 39,40 ] Bambach [ 41,42 ] derived the mean crushing force prediction expressions of CFRP‐metal hybrid square tube from a series of quasi‐static axial compression experiments and compared them with the experimental results. Zhang et al, [ 43 ] Wang and Lu, [ 44 ] also presented prediction models similar to Wierzbicki et al [ 39 ] The former put forward a formula for predicting the folding angle of SFE in the hybrid tubes, the latter took into account the influence of winding angles on energy absorption, and was also suitable for hybrid circular tubes under dynamic impact load.…”
Section: Introductionmentioning
confidence: 99%
“…They also concluded that there are three dominant failure modes, among which the progressive stable crushing mode results in a more beneficial mean force. 17 Hanefi et al 18 was one of the pioneers of exploiting reinforced metal-composite walls as energy absorbers. Moreover, energy absorbers with different fiber reinforcements were also studied in.…”
Section: Introductionmentioning
confidence: 99%